Rectal metastasis from bladder urothelial carcinoma: a case report - Yuki Ii; Shinya Munakata; Kumpei Honjo; Masaya Kawai; Shingo Kawano; Kiichi Sugimoto; Shuji Isotani; Yutaka Kojima; Shigeo Horie; Takashi Yao; Kazuhiro Sakamoto (Surgical Case Reports)
Abstract Background Urothelial carcinoma arises from transitional cells in the urothelial tract. In advanced cases, it can metastasize locally to surrounding organs or distally to organs such as the lungs, bones, or liver. Here we describe a case of rectal metastasis from urothelial carcinoma treated with multiple sessions of transurethral resection of bladder tumor (TURBT). Case presentation A 72-year-old woman presented to our department with abdominal bloating andobstructed defecation. She had undergone two sessions of TURBT for early urothelial carcinoma in another hospital at 64 and 65 months ago, respectively. Cystoscopy at 3 months after the second TURBT session had indicated disease recurrence, and thus, she had been referred to our hospital for further examination, followed by TURBT for the third time at 59 months ago and for the fourth time at 48 months ago; thereafter, she had been followed up with cystoscopy every 6 months without any recurrence. However, she returned to our hospital, complaining of difficult defecation. Subsequent colonoscopy demonstrated an obstructive tumor in the rectum, which was pathologically diagnosed as metastatic urothelial carcinoma of the bladder. Laparoscopic examination revealed two small areas of peritoneal dissemination in the pelvis. A sigmoid colostomy was performed without rectal tumor resection. She has been receiving chemotherapy and is still alive 10 months after surgery. Conclusions Rectal metastasis is a rare site of metastasis for urothelial carcinomas. It is important to consider the possibility of annular rectal constriction caused by infiltrating or metastasizing urothelial carcinoma when managing patients with urothelial carcinoma and with difficult defecation.